Synthetic and spectroscopic studies of 1,4-benzodiazepine analogues - Mphahlele, Malose Jack (Rhodes University, Faculty of Science, Department of Chemistry, 1994)
In this project, an extensive range of benzodiazepine analogues have been synthesised via Schmidt reaction of specially prepared flavanone, 4-quinolone and l-thioflavanone precursors; nitrogen insertion being effected by use of trimethylsilyl azide in trifluoroacetic acid. In some cases, several of the benzodiazepine analogues have also been prepared by alternative cyclisation routes. A detailed kinetic-mechanistic study of the Schmidt reaction of flavanones has been carried out using 'H NMR spectroscopy to explain the observed regiochemistry of nitrogen insertion. The reaction rates, for the formation of both amide and tetrazolo derivatives have been found to be influenced by the electronic effects of the A- and B-ring substituents. A series of benzodiazepine analogues have been shown to undergo regioselective A-ring chlorination with t-butylhypochlorite; the products being characterised by 'H NMR, IR and mass spectroscopy. The mass spectrometric fragmentation patterns of series of 2-aryl-4-quinolones, and 2-aryl-l ,4-benzodiazepinones and their tetrazolo[l ,5-dl analogues have been elucidated using a combination of low-resolution, high-resolution and metastable-peak analyses. The binding affinities of various benzodiazepine analogues for rat brain benzodiazepine receptors have been evaluated using a radioreceptor assay technique. Structure-activity relationships were investigated to establish the effects of various A-, B- and Coring substituents on binding affinity. The conformational preferences of selected systems have been studied using a combination of multi-pulse 'H NMR spectroscopy, X-ray crystallography and computer modelling techniques with a view to establishing the influence of conformation on binding affinity.
Keywords: Benzodiazepines; Tranquilizing drugs